Potential of Palm Oil Fuel Ash (POFA) Layers as Secondary Raw Material in Porcelain Stoneware Application / Azlan Zainudin...[et al.] - Zainudin, Azlan; Chee, Kiong Sia; Pauline, Ong; Narong, Oh Lai Ching; Muhd Nor, Nik Hisyamudin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Porcelain stoneware is a product produced from kaolinite clay, quartz, and feldspar. This paper studies the potential of POFA layers as a secondary raw material in the porcelain stoneware application. POFA was separated to four layers. Each layer was investigated by using scanning electron microscopy (SEM) and energy dispersive X-Ray spectroscopy (EDX) in order to analyse the microstructure images and elemental analysis of POFA layers. The result was compared to all basic raw materials of porcelain stoneware for a benchmark. The result shows that the fourth layer has the largest silica content. It is the layer that has a characteristic close to the real porcelain stoneware. The microstructure and elemental analysis of POFA layers are compared with previous finding of POFA. There is little published information on POFA layers but certain POFA layers have approached the result of published POFA.